THE IMPLEMENTATION OF INSTAGRAM SOCIAL MEDIA AS AN EFFORT TO IMPROVE POETRY WRITING SKILLS IN GRADE X STUDENTS OF YAPIN KERTASEMAYA VOCATIONAL HIGH SCHOOL FOR THE ACADEMIC YEAR 2022/2023 - Musyarofah, Musyarofah; Subaweh, Ahmad Maskur; Efendi, Irfan (Transpublika Publisher, 2023)
This research investigates the application of Instagram social media to enhance poetry writing skills among Class X students at SMK YAPIN Kertasemaya during the academic year 2022/2023. The study, focusing on 14 students in the ASKEP class, addresses the identified deficiency in poetry writing proficiency within the school. The research aims to answer two key questions: 1) How does the application of Instagram social media impact learning in poetry writing? 2) What is the effect of Instagram social media on the improvement of learning outcomes in poetry writing? The research employs a classroom action research methodology, with 14 Class X students as subjects. Data collection involves observations and tests conducted in two cycles. The findings reveal a notable enhancement in the process of learning poetry writing skills. In Cycle I, the average test score was 70, and it increased to 73 in Cycle II, indicating a positive progression. Consequently, the research concludes that the implementation of Instagram as a learning tool effectively improves poetry writing skills among Class X ASKEP students at SMK YAPIN Kertasemaya, influencing positive behavioral changes in the students' approach to writing poetry.